Identifikasi Staphylococcus aureus Pada Abon Sapi Di Pasar Pahing Kota Kediri - Mastuti Widianingsih; Dian Catur Setyorini (Universitas Muhammadiyah Surakarta, 2019)
Contamination of processed beef foods such as abon can be caused by various types of microbes, one of which is Staphylococcus aureus. Staphylococcus aureus can cause various infections, both on the skin, gastrointestinal tract, or endocarditis. The objective of this research was to determine the presence of Staphylococcus aureus in beef abon sold in Pahing Market, Kediri. Abon used is non-branded beef abon which is as many as 10 samples obtained by total sampling technique. Samples were tested by observation of colony morphology through Gram staining, mannitol fermentation test, catalase and coagulase test, and acetoin test. The samples were inoculated on Broth NaCl (ink. 24 hour-37°C), then inoculated on MSA (ink. 24 hour-37°C), and VP (ink. 2x24 hours-37°C). Catalase and coagulase tests were carried out by taking colonies on MSA media. The results showed that there were 9 abon samples contaminated with Staphylococcus aureus as indicated by Gram positive staining results, positive (perfect) mannitol fermentation, and positive acetoin, catalase, and coagulase test. The causes of contamination are contaminated abon ingredients, the manufacturing process using less sterile tools, poor handling and processing, processing food with dirty hands, food stored without cover, sick food processors, and dirty markets